2002
DOI: 10.1136/qhc.11.4.335
|View full text |Cite
|
Sign up to set email alerts
|

Patients' experiences and satisfaction with health care: results of a questionnaire study of specific aspects of care

Abstract: Objective:To determine what aspects of healthcare provision are most likely to influence satisfaction with care and willingness to recommend hospital services to others and, secondly, to explore the extent to which satisfaction is a meaningful indicator of patient experience of healthcare services. Design: Postal survey of a sample of patients who underwent a period of inpatient care. Patients were asked to evaluate their overall experience of this episode of care and to complete the Picker Inpatient Survey qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
443
5
23

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 537 publications
(500 citation statements)
references
References 7 publications
(6 reference statements)
29
443
5
23
Order By: Relevance
“…However, the most important determinants, as indicated by the regression, appear to be physical comfort, emotional support, and respect for patient preferences (9). A study conducted in rural Bangladesh has revealed that a significant proportion of users (34.2%) were not satisfied with the length of time that the facilities were open to the pubic, (28.2%) not satisfied with the time they wait to receive the service and 19.5% of users, who were almost all women felt privacy to be necessary, however privacy was maintained for less than half (45.1%) of these clients (10).…”
Section: Client Satisfaction and Associated Factorsmentioning
confidence: 98%
“…However, the most important determinants, as indicated by the regression, appear to be physical comfort, emotional support, and respect for patient preferences (9). A study conducted in rural Bangladesh has revealed that a significant proportion of users (34.2%) were not satisfied with the length of time that the facilities were open to the pubic, (28.2%) not satisfied with the time they wait to receive the service and 19.5% of users, who were almost all women felt privacy to be necessary, however privacy was maintained for less than half (45.1%) of these clients (10).…”
Section: Client Satisfaction and Associated Factorsmentioning
confidence: 98%
“…15 Likewise, satisfaction with dental services is similar to satisfaction with in-patient NHS care. 16 Dissatisfaction was higher among younger people, problem motivated and irregular attendees. Discontent about dental services is likely to be a key factor that influences dental service use.…”
Section: Complaints: Who They Would Contact First?mentioning
confidence: 99%
“…6,7 However, the strongest and most consistent finding is for age, with a positive relationship between increasing age and higher levels of satisfaction. 1,[6][7][8][9][10] Lower educational level is also linked to higher satisfaction levels, however this relationship is weaker. 1,7 Results for other demographic variables such as sex, income, marital status, and race tend to be inconsistent.…”
mentioning
confidence: 99%